A flexibilização das normas trabalhistas: uma análise da eficácia dos modelos de flexibilização vigentes e o impacto ocasionado na Economia com reflexos nas relações de trabalho - FEITOSA, Catia da Silva (2016)
The interest in academic work lies about the investigations into the economic system and labor relations when it comes to relaxation of labor standards that largely influence these relationships, with the elements, two of the main components of factors of production, capital and labor, both of which compose the productive system as a whole. Thus, the flexibility of labor regulations has caused impacts on both economic aspects and legal, arising from the world of work, compared to existing structures in the capitalist system: the infrastructure, the economy and the superstructure, the law. Thus, the issue of flexibility of labor relations, must be understood in the face of a dynamic model, within the current economic system, representing the one hand, the progress in our country (even in regard to the scope of its constitutional and legal limits existing), and on the other hand has been presented as a disguised way of achieving the established rights of workers and enshrined for decades, right now, especially dedicated to workers and that may be deregulated. Within this scientific study of perspective, the aim is thus, through this theme the verification of existing models, on which rests the very issue about flexibility, front stir mitigate the social costs, as an essential precondition for the arguments of employers in As regards the question that it would cause the creation of new jobs and consequently so would create more jobs, thus causing higher income in society and even lowering the unemployment rate.